2011 IEEE Vehicle Power and Propulsion Conference 2011
DOI: 10.1109/vppc.2011.6043187
|View full text |Cite
|
Sign up to set email alerts
|

Addressable and energy management system for the built environment (I)

Abstract: The increasing awareness for a cleaner earth has created more interests in the electric vehicle (EV) technology. Electric vehicles (EVs) will not only cause a reduction in our current greenhouse gas emissions, but also stop or reverse the trend at which our natural resources are being depleted. However, the introduction of the EVs into our societies will still require energy usage in the form of electricity. Integration of charging infrastructures will eventually be required in the built environment for these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
1
0
Order By: Relevance
“…Transport has a crucial role in the development and daily life of our societies [49]. However, it remains an essential source of harmful air pollutants [50,51], surpassing onefifth of global CO 2 emissions in 2021 [52][53][54] (21-23%, depending on the source).…”
Section: Transport and The Built Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Transport has a crucial role in the development and daily life of our societies [49]. However, it remains an essential source of harmful air pollutants [50,51], surpassing onefifth of global CO 2 emissions in 2021 [52][53][54] (21-23%, depending on the source).…”
Section: Transport and The Built Environmentmentioning
confidence: 99%
“…International and national authorities are showing signs of commitment to ensuring zero-emission new car sales in the next decade [121]. EV market share is also steadily increasing and it is expected that GHG emissions, air pollution, and the depletion of natural resources for the production of fossil fuels will slowly decline [49,122].…”
Section: Vehicle Electrificationmentioning
confidence: 99%
“…The researchers also apply this method in an interactive and continuous approach, instead of offline approach as used by other researchers, for energy auditing purposes. Additional information for a wide range of research in this field can also be found in [21][22][23][24][25][26][27].…”
Section: Monitoring At the Building Levelmentioning
confidence: 99%